2016
DOI: 10.1002/poc.3538
|View full text |Cite
|
Sign up to set email alerts
|

Experimental (FT‐IR) and theoretical (DFT) studies on prototropy and H‐bond formation for pyrazine‐2‐amidoxime

Abstract: The results of the first structural studies (with the use of both experimental and theoretical methods) on pyrazine‐2‐amidoxime (PAOX) were shown and discussed. FT‐IR spectra were recorded in different concentrations of the PAOX in apolar solvent to check the possibility of the inter‐ or intramolecular hydrogen‐bond formation. All possible tautomers–rotamers of PAOX were then theoretically considered at the DFT(B3LYP)/6‐311+G** level in vacuo. For selected isomers, calculations were also performed at higher le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Thus, Ungnade et al in 1958, based upon IR and 1 H NMR data, erroneously concluded that amidoximes exist exclusively in ( E , Z )‐ IHA form . Later, Tavakol et al (at the B3LYP/6‐311++G(d,p) and B3LYP/aug‐cc‐pVTZ levels of theory) and Makowski et al (at the B3LYP/6‐311+G(d,p), B3LYP/6‐311+G(3df,2p), and G3B3 levels of theory) conducted theoretical studies of the ( Z )‐ AO ⇌ ( E , Z )‐ IHA equilibrium and concluded that ( Z )‐ AO form is substantially more stable than ( E , Z )‐ IHA form. These theoretical calculations deals with the only 1 stereoisomer for each form and ( E )/( Z )‐tautomerism of both amidoxime and iminohydroxylamine species was not considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Ungnade et al in 1958, based upon IR and 1 H NMR data, erroneously concluded that amidoximes exist exclusively in ( E , Z )‐ IHA form . Later, Tavakol et al (at the B3LYP/6‐311++G(d,p) and B3LYP/aug‐cc‐pVTZ levels of theory) and Makowski et al (at the B3LYP/6‐311+G(d,p), B3LYP/6‐311+G(3df,2p), and G3B3 levels of theory) conducted theoretical studies of the ( Z )‐ AO ⇌ ( E , Z )‐ IHA equilibrium and concluded that ( Z )‐ AO form is substantially more stable than ( E , Z )‐ IHA form. These theoretical calculations deals with the only 1 stereoisomer for each form and ( E )/( Z )‐tautomerism of both amidoxime and iminohydroxylamine species was not considered.…”
Section: Resultsmentioning
confidence: 99%
“…Makowski et al also studied the tautomerization of pyrazine‐2‐carbamidoxime to the fouth tautomeric form, viz, the nitroso form (Figure ; ANC ), and found that this form is by 31.4 kcal/mol less favorable than the amidoxime form . Głębocka et al also shown that the ( E )‐form of the amidoxime is less favorable than the ( Z )‐form, but isomerism of the ( E )‐configured amidoxime was not studied.…”
Section: Resultsmentioning
confidence: 99%
“…Recent theoretical and experimental studies show that the most stable and dominant form is the Z -amidoxime [15,16,18]. This isomer is more stable than the iminohydroxylamine, the aminonitrone and the nitroso-amine, the latter being the less stable [18].…”
Section: Isomerism Of Amidoximes and Oximesmentioning
confidence: 99%
“…Recent theoretical and experimental studies show that the most stable and dominant form is the Z -amidoxime [15,16,18]. This isomer is more stable than the iminohydroxylamine, the aminonitrone and the nitroso-amine, the latter being the less stable [18]. However, according to the most recent published work on that topic [16], three amidoximes isomers may coexist due to their close relative energies: the Z -amidoxime as the most stable form in both protic and aprotic solvents with the Z -aminonitrone and the E -amino oxime as the minor forms.…”
Section: Isomerism Of Amidoximes and Oximesmentioning
confidence: 99%
“…activity forced us to generate and applicate of a new research approach. Firstly, the pathogens were changed in tests based on the predicted similarity of unknown 3,6-PIRAMICAR to pyrazine derivatives antifungal action (selectivity against Candida albicans) studied in our previous research [15][16][17][18] . Additionally, we applied the pH conditions analogy (values lower than 5.5) for the pyrazinamide activation.…”
mentioning
confidence: 99%